PENINGKATAN KEMAMPUAN PENALARAN MAHASISWA CALON GURU MATEMATIKA DALAM PEMECAHAN MASALAH MELALUI PEMBELAJARAN PROBLEM POSING - Sanapiah, Sanapiah; Kurniawan, Ade (Universitas Pendidikan Mandalika (UNDIKMA), 2016)
This study aims to identify improving students' math reasoning abilities through learning problem posing in problem solving at students of Mathematics Education Department of FPMIPA IKIP Mataram. The lack of basic knowledge and reasoning ability of mathematics teacher candidate in solving school math problem become the main factor of this research. Therefore, one of the learning methods that can be applied to solve the problem is through problem posing method. This research is Quasi Eksperimen research with Time Series design. The subject of this research consists of 35 mathematics teacher candidates consisting of 18 science students and 17 non-IPA students. The research instrument used consisted of questionnaire, written test (pretest and postest), observation and interview. The validity of the written test description is done through field trials and two validators. Field test results will be used to determine the differentiation, difficulty, validity, and reliability of the test. The data of the writing test were analyzed by using t-test. The result of this research shows improvement of students' reasoning ability in solving problems involving geometry material after applied problem posing (problem solving) method. This increase in reasoning is derived from the problem-solving process of student teacher problem in a structured way.